It was a Faint Dream - Jissoji, Akio; Nakabori, Masao; Hatta, Janet; Kishida, Shin; Terada, Minori (Akio Jissôji: The Buddhist Trilogy, 2019)
Following his ultramodern Buddhist Trilogy, Akio Jissôji casts himself back to the Kamakura era for a tale of desire and misuse in "It Was a Faint Dream". Taking its name from a Heian era Buddist ode to transience, "Faint Dream" follows its melancholy heroine on a fleeting path of love, loss, romantic disappointment, and finally spiritual rebirth while the nation faces the external threat of putative invasion by warlike imperialists hellbent on domination and conquest. [windowsonworlds.com]